Impact of some chemical treatments and length of storage on the storability of sugar beet - Zubi, Hussien Al; Jbawi, Entessar Al; Jeddawi, Sameer Al; Tahla, Mohammad Khair; Ismaiel, Raafat; Huniesh, Thamer Al; Aliesha, Gaidaa; Radwan, Radwan; Azzam, Hasan (International Journal of Environment, 2016)
An experiment was conducted at the Agricultural Research Center of Al Ghab, General Commission for Scientific Agricultural Research (GCSAR), Syria, to evaluate the effect of some chemical application on the sugar losses reduction, and some quality traits in 2014/2015 season. Three slaked lime concentrations of 5, 10 and 15 percent, and three concentrations of calcium chloride of 2, 4, and 6%, and a mix of 5% slaked lime with 2% calcium chloride, beside the check (no treatment) (factor C). The second factor (D) was the storage durations of 6 days, and tow varieties (Factor V) were arranged as factorial experiment in RCBD with four replications. The varieties one of them was monogerm (Vico), while the other was multigerm (Reda), they were drilled in mid November, and storage roots were harvested late August. Weight percent loss and quality of beet samples such as sugar content, total soluble solids (TSS %), and purity% were determined throughout storage period. The results of analysis of variance ANOVA showed that effect of varieties was significant for TSS (brix %), sucrose%, root weight loss (P<0.05). All the studied traits were affected significantly (P<0.05) by storage duration. Chemical treatments had significant effect on all the studied traits (P<0.05), and the best treatment was with calcium chloride 6%. The percentage of variance confirmed that the most effective factor for the all studied traits was the storage period, followed by the varieties, and finally in a very low percent was the chemical treatments, because of that it is very urgent to send the harvested roots immediately to the factories to be processed within 24 hours, or treated with calcium chloride of 6% to preserve the sugar content as possible till manufacturing. Also the study concluded that the mutigerm variety Reda deteriorated less that the monogerm variety Vico, so Reda is recommended to be stored if necessary. International Journal of Environment Vol. 5 (1) 2016, pp: 96-106